2016
DOI: 10.1016/j.chemgeo.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Acid-dissolution of antigorite, chrysotile and lizardite for ex situ carbon capture and storage by mineralisation

Abstract: Serpentine minerals serve as a Mg donor in carbon capture and storage by mineralisation (CCSM).The acid-treatment of nine comprehensively-examined serpentine polymorphs and polytypes, and the subsequent microanalysis of their post-test residues highlighted several aspects of great importance to the choice of the optimal feed material for CCSM. Compelling evidence for the nonuniformity of serpentine mineral performance was revealed, and the following order of increasing Mg extraction efficiency after three hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 50 publications
(64 reference statements)
5
17
0
Order By: Relevance
“…On the other hand, the low extraction efficiencies of Mg reported can be attributed to the competing presence of Fe and Al in the sample. This phenomenon observed was similar to that reported by Lacinska et al [42], in which they cited the presence of Al 3+ ions as the hindering factor in the release of Mg + , primarily due to the promotion of layer-to-layer linkage by H-bonding, which kept the Mg + ions bound to the solid. The preferential leaching of Fe 3+ in comparison to Mg + has also been observed in samples where both ions are present, such as in antigorites, thus contributing to low Mg extraction rates [37].…”
Section: Ion Extraction Efficienciessupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, the low extraction efficiencies of Mg reported can be attributed to the competing presence of Fe and Al in the sample. This phenomenon observed was similar to that reported by Lacinska et al [42], in which they cited the presence of Al 3+ ions as the hindering factor in the release of Mg + , primarily due to the promotion of layer-to-layer linkage by H-bonding, which kept the Mg + ions bound to the solid. The preferential leaching of Fe 3+ in comparison to Mg + has also been observed in samples where both ions are present, such as in antigorites, thus contributing to low Mg extraction rates [37].…”
Section: Ion Extraction Efficienciessupporting
confidence: 90%
“…In addition, the presence of rod-shaped particles in Figure 4b suggests the presence of lizardite in the sample as verified by the spike of Mg in the EDX elemental analysis. The presence of silicon is also verified for both samples, particularly for the region bearing spherical particles and is consistent with existing data related to wastes and ores derived from mines [12,[41][42][43][44].…”
Section: Morphological Propertiessupporting
confidence: 89%
“…However, the Al 3+ level reported by Daval et al (2013) was 0.88% in the form Al 2 O 3 . According to Lacinska et al (2016), lizardite 1T with low Al 2 O 3 (1%) levels, lead to higher Mg extraction than lizardite 1T with high Al 2 O 3 levels (2.36%). Since the lizardite used by Daval et al (2013) had low Al 2 O 3 levels, the low extraction could be caused by the large particle size of the material used (500-800 μm).…”
Section: Comparison Of Results Obtained With Published Datamentioning
confidence: 99%
“…While there have been many studies in this field, there is still a discrepancy regarding CO 2 capture potential of silicate rocks. In order to get a better understanding of whether or not silicate rocks are adequate, recently Gadikota et al (2014b); Lacinska et al (2016); Lavikko and Eklund (2016); Styles et al (2014) have suggested that silicate rocks must be characterized more carefully because their mineralogy varies widely. The characterization must consider pore structure, surface area (S BET ), origin, subsequent metamorphic changes, and crystal structure of the minerals in the rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many materials tested, magnesium-rich materials are thought to be good candidates for carbonation due to their natural abundance [14] and relatively higher unit mass binding efficiency (e.g., as compared to calcium). For example, physical activation (grinding [15][16][17] or heating [18,19]), chemical leaching (acid [20][21][22], recyclable ammonium salt [23,24] or non-acidic ionic solutions [25]), bioleaching [26,27] were applied to Mg rich minerals to dissolve and concentrate Mg. However, the other CO 2 absorption and carbonate precipitation steps have been less explored.…”
Section: Co 2 Mineral Sequestrationmentioning
confidence: 99%